2021
DOI: 10.1016/j.sjbs.2021.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new sources of resistance to resistance-breaking isolates of tomato spotted wilt virus

Abstract: The tomato as both a fresh consumption and industrial product is one of the most profitable vegetables and has a large cultivation area in the world. Parallel to intense production activities, Tomato Spotted Wilt Virus (TSWV), like viral diseases, results in significant economic losses every year. Use of resistant cultivars is the most efficient and environmental-friendly method of fighting against these diseases. This study was conducted to develop new tomato genetic resources resistant to TSWV because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In Turkey, PMMoV has been identified on pepper several times since 2013 (Caglar et al 2013). In a study conducted in Antalya, it was reported that genes that provide monogenic resistance to TSWV such as Tsw and Sw-5 become inactive at high temperatures and the state of resistance disappears (Kabas et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, PMMoV has been identified on pepper several times since 2013 (Caglar et al 2013). In a study conducted in Antalya, it was reported that genes that provide monogenic resistance to TSWV such as Tsw and Sw-5 become inactive at high temperatures and the state of resistance disappears (Kabas et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although new sources of resistance to RB strains have been recently reported in some wild tomato accessions (Kabaş et al 2021), at this time, cultivars carrying these resistance genes are not yet available, and thus, it is advisable…”
Section: Morphological Assessmentmentioning
confidence: 99%
“…Mechanical inoculation is a simple and effective method for conducting genetic re search on resistance to TSWV. A large number of plants can be quickly screened simulta neously with several isolates for the identification of resistant resources [35,36]. An inoc ulation buffer containing potassium phosphate buffer (0.1 M, pH 7.0), sodium sulphite (0.2% w/v), and polyvinyl pyrolidon (2% w/v) was used.…”
Section: Mechanical Inoculationmentioning
confidence: 99%